GO et l’injonction : le cas de GO AND V - Catherine Collin (Corela)
The use of GO-AND-Verb is very common in contemporary English. This study wants to analyse the role of the GO-AND injunctions in a corpus of journalistic prose. The GO-ANDVerb structure is then to be understood as a global and complex predicate. This use of GO in coordinated structure is never to be equated to successive processes.